An Analysis Of Communication Strategies Used By English Tutorial Program Students In Speaking Class: Naturalistic Study At Departement Of Accounting Education At Muhammadiyah University Of Surakarta - Puspitasari, Dara, Prof.Endang Fauziati, M.Hum (2017)
ABSTRACT This study decribed communication strategies used by English Tutorial Program students in speaking class: naturalistic study at Accounting Education Departement at Muhammadiyah University of Surakarta. This study described three 2 components, (1) The type of communication strategies used by students, (2) Frequency the type of communication strategies, and The dominant communication strategies used by students. The data of this study consist of communication strategies used by English Tutorial Pogram students in speaking class at Accounting Departement at Muhhamadiyah University of Surakarta. Researcher uses 3 groups of English Tutorial Program with 30 students as a subject. This study used descriptif kualitatif. The researcher analyzed the data using Dornyei's Taxonomy. The researcher found 2 types with six subtypes of Dornye's Taxonomy. The dominant type used by the students is Stalling or Time Gaining with 56,49%, Code Switching, Appeal For Help, Message Abandonment, Literal Translation, and the rarely type used by students is Non-Linguistic Signals with 1,67%. It can be concluded that communication strategy taken by students can be used as materials in speaking class. So, students can communicate fluently. Keyword : Speaking, Communication Strategies